Information warfare in the age of cyber conflict - Whyte, Christopher, 1988-; Thrall, A. Trevor; Mazanec, Brian M. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book examines the shape, sources and dangers of information warfare (IW) as it pertains to military, diplomatic and civilian stakeholders. Cyber warfare and information warfare are different beasts. Both concern information, but where the former does so exclusively in its digitized and operationalized form, the latter does so in a much broader sense: with IW, information itself is the weapon. The present work aims to help scholars, analysts, and policymakers understand information warfare within the context of cyber conflict. Specifically, the chapters in the volume address the shape of influence campaigns waged across digital infrastructure and in the psychology of democratic populations in recent years by belligerent state actors, from the Russian Federation to the Islamic Republic of Iran. In marshalling evidence on the shape and evolution of information warfare as a broad-scoped phenomenon aimed at societies writ large, the authors in this book present timely empirical investigations into the global landscape of influence operations, legal and strategic analyses of their role in international politics, and insightful examinations of the potential for democratic process to overcome pervasive foreign manipulation. This book will be of much interest to students of cyber-security, national security, strategic studies, defence studies and International Relations in general"--
Part 3: Building resilience: Questions of legality, diplomacy and society -- Might or Byte(s): On the safeguarding of democracy in the digital age / Christopher Colligan -- On the organization of the U.S. Government for responding to adversarial information warfare and influence operations / Herbert Lin -- Virtual disenfranchisement : Cyber election meddling in the grey zones of international law / Michael Schmitt -- Stigmatizing cyber and information warfare : Mission impossible? / Brian Mazanec and Patricia Shamai -- Part 4. The fluid shape of modern information warfare -- How deep the rabbit hole goes : Escalation, deterrence and the 'deeper' challenges of information warfare in the age of the internet / Christopher Whyte.
OCLC-licensed vendor bibliographic record.
Keywords: Information warfare; Disinformation; Propaganda -- Technological innovations; Propaganda, International -- History -- 21st century; Disinformation -- United States -- History -- 21st century; Democracy; Social media -- Political aspects; Cyberspace -- Political aspects; Disinformation -- Government policy; United States -- Politics and government -- 21st century; HISTORY / Military / Strategy; POLITICAL SCIENCE / Political Freedom & Security / International Security; POLITICAL SCIENCE / Political Freedom & Security / General; political warfare -- influence campaigns